Thermal Simulations of Drilling of Cryogenic Lunar Soils Containing Water Ice - Jinsheng Cui; Baoxian Chen; Sibo Liu; Deming Zhao; Weiwei Zhang (Aerospace, 2023)
Water ice is an important water source in lunar polar soil. Drilling and sampling lunar polar soil are important engineering tasks of lunar exploration. In view of the influence of temperature rise on the quality of samples obtained by drilling, the heat transfer and temperature rise in drilled ice-containing lunar soil were investigated. In this study, a thermal simulation model for drilling lunar soil was established based on the discrete element method (DEM). Simulations of the drilling temperature of lunar soil containing ice at 3–5% were performed assuming normal pressure and low temperature. After validating the feasibility and accuracy of the simulation method, the temperatures of the drilling tools and lunar soil were analyzed. Furthermore, drilling in a vacuum was simulated as well, and the results indicated that ice sublimation was negligible for reasonable drilling procedures in the current study.